Persepsi Mahasiswa Program Studi Pendidikan Administrasi Perkantoran terhadap Model Pembelajaran Project Based Learning (PjBL): Penelitian - Furqan Young; Jara Fajira; Nilam Artika Sari; Nurul Khoirunnisa; Andi Taufiq Umar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study employs a descriptive quantitative approach to examine the perceptions of 40 students majoring in Office Administration Education regarding the Project-Based Learning (PjBL) model. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics (percentages, means, and frequency distributions). The findings indicate a generally positive perception of PjBL, particularly in terms of conceptual understanding and its benefits/effectiveness. Although a small number of students encountered challenges in time management and collaboration, overall, PjBL was perceived as effective in enhancing both academic and non-academic skills especially self-confidence, problem-solving, and teamwork. These findings suggest that the implementation of PjBL is relevant to the needs of the modern workforce and can effectively increase student engagement in vocational learning processes.